Ethnographic Stories for Market Learning. (July 2013) - Cayla, Julien; Arnould, Eric
Although ethnography has become a popular research approach in many organizations, major gaps exist in the field's understanding of the way it operates in the corporate world, particularly in how ethnography facilitates market learning. Drawing from extensive fieldwork in the world of commercial ethnography, the authors describe how ethnographic stories give executives a unique means of understanding market realities. By working through the rich details of ethnographic stories infused with the tensions, contradictions, and emotions of people's everyday lives, executives are better able to grasp the complexity of consumer cultures. Overall, this research should help managers leverage the catalytic effects of ethnographic storytelling in their efforts to learn about and understand market contexts.